Sustainable Coastal Tourism Practices in Aklan: Bases for Policy Recommendations - Estuya, Probee Bea; De Jose, Tonylen (Journal of Interdisciplinary Perspectives, 2024)
Aklan, one of the provinces in the Philippines, is known for its beautiful white beaches. Among its municipalities, Buruanga stands out with its immaculate white sand. This study examined the current state of coastal tourism, identified challenges and opportunities, and proposed policy recommendations for the effective implementation of sustainable practices in Aklan, Philippines. The research, conducted through a quantitative descriptive correlational design, involved 30 stakeholders, including resort owners, tourists, resort workers, municipal tourism officers, and local government officials. Data were collected using a researcher-made questionnaire and interviews. Findings revealed positive implementation of sustainable practices, particularly in policies, operations and management, socio-cultural aspects, products and services, and facilities. However, challenges persisted, such as changing existing practices and waste management. Despite these challenges, opportunities existed, including existing infrastructure and collaboration between stakeholders. Recommendations emphasized the need for strengthened waste management systems, updated policies, increased awareness campaigns, and community involvement. The study underscored a commitment to sustainable practices in Buruanga's coastal areas while identifying areas for improvement. Addressing these weaknesses can leverage existing strengths, contributing to a more environmentally responsible and economically viable tourism industry. Through its findings and recommendations, this research sought to inform policymakers, stakeholders, and communities, fostering sustainable tourism development in Buruanga, Aklan, and beyond.